Jayanta's Refutation to Buddhist Definition of Pramana - Tashi Dorjey (Soshum: Jurnal Sosial dan Humaniora, 2019)
It is a well established fact that India has been the center of famous thinkers and philosophers right from the ancient time as a result of its various philosophical traditions. These branches of thought are deeply embedded in the Indian culture and are commonly categorized as the six orthodox and the three heterodox systems of Indian philosophy. The concept of epistemology has been the topic of heavy discussion as scholars in the past have agreed or strongly disagreed on their formulations of the different schemes of metaphysics. For Indian philosophers knowledge is a means to reach at ultimate truth through speculation and experience. In this paper I am going to present the Jayanta’s refuration to Buddhist concept of pramāṇa.